The quality of the service and its influence on the satisfaction of the students of the Faculty of Legal and Business Sciences of the Jorge Basadre Grohmann National University of Tacna, 2012-2013. - Alférez Asencios, Jerzy (2014)
Objective: The present research was conducted in order to determine the influence of quality of service on students´ satisfaction of The Faculty of Business and Judicial Sciences of Jorge Basadre Grohmann National University of Tacna. Method: The work corresponds as a basic research type and correlational level. For this purpose it was considered information obtained through the application of the questionnaire measuring instrument for assessing the quality of service and satisfaction provided in The Faculty of Business and Judicial Sciences, which were applied to students with technical survey, using the Likert scale. After the phase of analysis and interpretation of the results was determined that in the Faculty Business and Judicial Sciences, quality of service influences on students´ satisfaction. The measurement model has 10 indicators of quality of service and 22 indicators for students´ satisfaction. Result: They have determined that quality of service is perceived as negative by 49.97%, 16.71% is perceived as positive and 33.32% is indifferent. In other hand, students satisfaction, 30.47% are satisfied, 33.15% are insatisfied and 36.38% are indiferent. Conclusions: Quality of service dimensions as tangible elements, fiability, answer capability, security and empathy are perceived as poor quality, and satisfaction dimensions as learning and teaching methods, organization and infrastructure career Faculty indicate insatisfaction, while the dimensions and teaching equipment evaluations indicate indifference of Students